Rejestracja zbioru danych osobowych ze szczególnym uwzględnieniem ochrony wizerunku kibica uzyskanego w ramach odbywania się meczów piłkarskich jako publicznoprawny obowiązek administratora - Bączyk, Jarosław (Kwartalnik Prawa Publicznego, 2016)
The scope of this article is to discuss the problem of football stadium monitoring in relations to the obligations resulting from the regulation of the Personal Data Protection Act. Stadium monitoring allows for recording of the image of participants in football matches (football fans). This issue raises two fundamental doubts: first of all, if the video record obtained from the monitoring system is subject to the provisions of the Personal Data Protection Act and, secondly, if such information is classified as protected personal data, what would mean, that the data controller is obliged to report such data to the General Inspector for Personal Data Protection.